Caracterização clínico-epidemiológica e espacial dos casos de dermatofitoses atendidos em um centro de referência em dermatologia sanitária - Camargo, Daniel do Carmo de [UNESP] (Mycopathologia, 2024)
Dermatophytes are fungi that use keratin as a nutritional source, and their clinical manifestations are called tinea. It is estimated that 25% of the world's population may be affected by dermatophytosis, but there are still gaps in the literature regarding the epidemiological and territorial characterization of these species. Therefore, we carried out an exploratory and retrospective study, based on the collection of information from medical records of patients diagnosed with dermatophytosis treated at the Instituto Lauro de Souza Lima (ILSL) between 2016 and 2020. The objective was to characterize the epidemiological and geospatial aspects of dermatophyte species and their relationship with climatic, geoenvironmental and social factors in the Epidemiological Surveillance Groups (GVE) in the state of São Paulo. The R Studio software was used for descriptive and analytical statistics, and the Quantum GIS 3.14 Biatowieża software for exploring the spatial distribution of species. Chapter 1 presented the proportion of species diagnosed in ILSL in the period from the 28 GVE. GVE XV Bauru concentrated 89.1% of cases, with the species Trichophyton rubrum being the most common (70.3%). The age group over 60 years was the most affected (41.4%), and in the group <15 years there was a higher occurrence of tinea capitis (69.2%). Chapter 2 investigated the occurrence of dermatophyte species regarding epidemiological, environmental, social and geospatial characteristics. Our findings suggest that the species identified in the study were located in regions with temperatures above 18ºC, characterized by humid and clayey soils within the phytogeographical domain of the Brazilian Cerrado. Notably, the species Microsporum canis and Trichophyton mentagrophytes predominantly affected individuals residing in areas of high social vulnerability. The occurrence of dermatophytes in different contexts, including seasonal, geoenvironmental and social factors, has provided insights into the epidemiology and dissemination of these fungi. More comprehensive and controlled studies can contribute to a deeper understanding of the factors that influence the spread and movement of hosts and dermatophyte species over time. This understanding is crucial for developing effective prevention and control approaches.

Os dermatófitos são fungos que utilizam a queratina como fonte nutricional, e suas manifestações clínicas são chamadas de tinea. Estima-se que 25% da população mundial possa ser acometida por dermatofitoses, mas ainda há lacunas na literatura acerca da caracterização epidemiológica e territorial dessas espécies. Assim, realizamos um estudo exploratório e retrospectivo, baseado na coleta de informações de prontuários de pacientes com diagnóstico de dermatofitoses atendidos no Instituto Lauro de Souza Lima entre 2016 a 2020. O objetivo foi caracterizar os aspectos epidemiológicos e geoespaciais de espécies de dermatófitos e sua relação com fatores climáticos, geoambientais e sociais nos Grupos de Vigilância Epidemiológica (GVE) do estado de São Paulo. O software R Studio foi utilizado para estatística descritiva e analítica, e o software Quantum GIS 3.14 Biatowieża para exploração da distribuição espacial das espécies. O capítulo 1 apresentou a proporção de espécies diagnosticadas no ILSL no período, provenientes dos 28 (GVE). O GVE XV Bauru concentrou 89,1% dos casos, sendo a espécie Trichophyton rubrum (70.3%) a mais frequente. A faixa etária acima de 60 anos foi a mais acometida (41,4%), e no grupo <15 anos houve maior ocorrência de tinea capitis (69,2%). O capítulo 2 investigou a ocorrência das espécies de dermatófitos quanto a características epidemiológicas, ambientais, sociais e geoespaciais. Nossos principais achados sugerem que as espécies identificadas no estudo estavam localizadas em regiões com temperaturas superiores a 18ºC, caracterizadas por solos úmidos e argilosos dentro do domínio fitogeográfico do Cerrado brasileiro. Notavelmente, as espécies Microsporum canis e Trichophyton mentagrophytes afetaram predominantemente indivíduos residentes em áreas de alta vulnerabilidade social. A ocorrência de dermatófitos em diferentes contextos, incluindo fatores sazonais, geoambientais e sociais, forneceu insights sobre a epidemiologia e os padrões de disseminação desses fungos. Estudos mais abrangentes e controlados podem contribuir para uma compreensão mais profunda dos fatores que influenciam a disseminação e movimentação de hospedeiros e espécies de dermatófitos ao longo do tempo. Esta compreensão é crucial para o desenvolvimento de abordagens eficazes de prevenção e controle.
Caracterización clínico-epidemiológica y espacial de casos de dermatofitosis atendidos en un centro de Referencia en dermatología sanitaria
Keywords: Dermatófitos; Dermatofitoses; Epidemiologia; Georreferenciamento; Tinea